2012
DOI: 10.1007/s00216-012-6212-3
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolism of five model drugs by fungi colonizing cadavers using LC-ESI-MS/MS and GC-MS analysis

Abstract: It is well-known that cadavers may be colonized by microorganisms, but there is limited information if or to what extent these microbes are capable of metabolizing drugs or poisons, changing the concentrations and metabolic pattern of such compounds in postmortem samples. The aim of the present study was to develop a fungal biotransformation system as an in vitro model to investigate potential postmortem metabolism by fungi. Five model drugs (amitriptyline, metoprolol, mirtazapine, promethazine, and zolpidem) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…MRT and its NFM show a cleavage through the piperazine moiety leaving fragments with m/z 195 and 209 (Figures a, d, and e) or m/z 211 and 225 (Figure b) representing the unchanged or hydroxylated tricyclic ring system, respectively. The hydroxy group in the latter metabolite (Figure b) is most likely attached to the aliphatic carbon atom of the methylene group between the two aromatic rings because the retention time of this metabolite differs from the hydroxyaryl metabolites previously reported by Martínez et al . The metabolites with pseudomolecular ions m/z 268 and unchanged tricyclic ring systems (Figures d and e) can be interpreted as combinations of N ‐demethylation and hydroxylation at the piperazine moiety because they have a prominent neutral loss of water in their EPI spectra.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…MRT and its NFM show a cleavage through the piperazine moiety leaving fragments with m/z 195 and 209 (Figures a, d, and e) or m/z 211 and 225 (Figure b) representing the unchanged or hydroxylated tricyclic ring system, respectively. The hydroxy group in the latter metabolite (Figure b) is most likely attached to the aliphatic carbon atom of the methylene group between the two aromatic rings because the retention time of this metabolite differs from the hydroxyaryl metabolites previously reported by Martínez et al . The metabolites with pseudomolecular ions m/z 268 and unchanged tricyclic ring systems (Figures d and e) can be interpreted as combinations of N ‐demethylation and hydroxylation at the piperazine moiety because they have a prominent neutral loss of water in their EPI spectra.…”
Section: Resultsmentioning
confidence: 80%
“…The metabolites with pseudomolecular ions m/z 268 and unchanged tricyclic ring systems (Figures d and e) can be interpreted as combinations of N ‐demethylation and hydroxylation at the piperazine moiety because they have a prominent neutral loss of water in their EPI spectra. Martínez et al . previously reported a human metabolite with the same pseudomolecular ion and fragmentation pattern to the latter two, but with different retention time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Enteric bacteria and invading bacteria and fungi in cadavers can metabolize drugs, causing postmortem changes of blood drug concentrations . In particular, an in vitro model showed that fungi known to colonize cadavers (e.g., Absidia repens and Mortierella polycephala) could metabolize drugs via demethylation, oxidation, and hydroxylation . As the primary route of 25B‐NBOMe metabolism is 5′‐demethylation, followed by conjugation to glucuronic acid , the redistributed 25B‐NBOMe from the lung to the blood might be degraded by colonizing microorganisms in the blood.…”
Section: Resultsmentioning
confidence: 99%